DETERMINASI SOSIAL LINGKUNGAN KERJA DAN EPIDEMIOLOGI RETENSI TENAGA KESEHATAN: TINJAUAN LITERATUR PERAN MEDIASI KOMITMEN ORGANISASI TERHADAP KOMPETENSI PERAWAT DI RSUD PROVINSI NTB - Baiq Nirmalasari; Yuly Peristiowati (Jurnal Cakrawala Ilmiah, 2026)
Background: Health worker retention, particularly among nurses, is a critical challenge for service stability at RSUD Provinsi NTB. As a referral hospital, the nurse turnover phenomenon is influenced by the interaction between environmental determinants and individual professional capacity. Objective: This study aims to analyze the social determinants of the work environment and the epidemiology of health worker retention by exploring the mediating role of organizational commitment on nursing competence. Methods: This study employed a Systematic Literature Review (SLR) method. Literature searches were conducted on Scopus and Google Scholar databases spanning 2016-2026. Primary articles were selected based on strict inclusion criteria using the PRISMA protocol. Results: Findings indicate that positive social determinants of the work environment significantly suppress resignation rates epidemiologically. Nursing competence is proven not to stand alone in influencing retention; organizational commitment mediation (especially affective commitment) is required to transform individual expertise into institutional loyalty. Organizational commitment functions as a bridge that strengthens the relationship between a supportive environment and the nurses' intention to stay. Conclusion: Retention strategies at RSUD Provinsi NTB must focus on strengthening the social work climate and competence development, accompanied by increasing employees' emotional attachment to the organization.